CULTURAL SOCIOLOGY - Borer, Michael (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Cultural sociology is an exciting and growing field in contemporary social inquiry. "Culture" is one of the most elusive words in the English language. On television, on the streets, and in lecture halls, "culture" is shorthand for a number of things, often with overlapping and sometimes contradictory meanings. This course will survey the major theoretical and methodological approaches to the "culture question." What is it, where does it come from, how does it change, and how does it work? Subjects to be explored include: religion and other belief systems; the differences and similarities between high and low culture; the mass media and other forms of communication; and the existence and significance of cultural distinctions such as race, ethnicity, gender, class, and lifestyle.